Artificial Intelligence Capability, Knowledge Sharing, and Organizational Innovation: A Systematic Literature Review and Future Research Agenda - Janeth Jacoby; José Martínez; Lidya Jareño (Global Insights in Management and Economic Research, 2026)
Purpose of the study: Artificial intelligence (AI) capability has emerged as a strategic organizational resource that enables firms to improve knowledge processes and innovation performance. However, empirical evidence explaining the relationship among AI capability, knowledge sharing, and organizational innovation remains fragmented. This study systematically reviews the existing literature to synthesize current knowledge and identify future research directions. Materials for Analysis: A systematic literature review (SLR) was conducted following the PRISMA 2020 guidelines. Literature searches were performed in Scopus, Web of Science Core Collection, and PubMed using predefined Boolean search strings. The review employed a two-stage screening process consisting of title and abstract screening followed by full-text eligibility assessment based on predefined inclusion and exclusion criteria. Four empirical studies published between 2022 and 2026 met all eligibility criteria and were included in the final qualitative synthesis. Results: The review consistently demonstrates that AI capability positively influences organizational innovation through enhanced knowledge-sharing processes. Knowledge sharing emerged as the principal mediating mechanism linking AI capability with innovation outcomes across different organizational contexts. Several studies further identified organizational cohesion, knowledge-sharing culture, and information governance as important contextual factors that strengthen the effectiveness of AI capability. Despite these consistent findings, the existing literature remains limited by cross-sectional research designs, a relatively small number of empirical studies, and a strong concentration of evidence from Asian countries. Conclusions: This review provides an integrated synthesis of the emerging literature on AI capability, knowledge sharing, and organizational innovation. It develops a comprehensive understanding of the mechanisms through which AI capability contributes to innovation while identifying theoretical and methodological gaps for future research. The findings offer practical implications for organizational leaders seeking to leverage AI capability as a strategic driver of innovation through effective knowledge-sharing practices.